2017
DOI: 10.24028/gzh.0203-3100.v39i4.2017.107506
|View full text |Cite
|
Sign up to set email alerts
|

Seismic visualization of plumes and super-deep fluids in mantle under Ukraine

Abstract: Введение. Согласно существующим в настоящее время представлениям [До-брецов, 2010; Хаин, 2010], новая концеп-ция глобальной геодинамики (тектоника) Земли включает в себя: а) тектонику плит, определяемую кон-векцией в верхней и нижней мантии и вза-имодействием астеносферы и литосферы; б) тектонику плюмов, зарождающихся на границе ядро-мантия и определяю-щих крупные магматические провинции (LIP), или горячие поля, по определению УДК 550.334 DOI: http://dx.doi.org/10.24028/gzh. 0203-3100.v39i4.2017.107506 Сейс… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The aim of this work is to analyze the data on the parameters of the modern BSB lithosphere obtained by us [Starostenko et al, 2015] and other researchers [Nikishin et al, 2015;Tsvetkova et al, 2017;Makarenko et al, 2021] in terms of their use as indicators of age and driving mechanisms of subbasin opening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this work is to analyze the data on the parameters of the modern BSB lithosphere obtained by us [Starostenko et al, 2015] and other researchers [Nikishin et al, 2015;Tsvetkova et al, 2017;Makarenko et al, 2021] in terms of their use as indicators of age and driving mechanisms of subbasin opening.…”
mentioning
confidence: 99%
“…Parameters of the lithosphere. The generalization of the parameters of the modern lithosphere of the Western and Eastern subbasins (Table 2) was performed according to our data [Starostenko et al, 2015;Rusakov, Pashkevich, 2017;Kutas, 2020] using data on the depth of the acoustic basement [Nikishin et al, 2015] and velocity characteristics of the subcrustal mantle [Tsvetkova et al, 2017].…”
mentioning
confidence: 99%
“…1. The position of the DDV in the structure of the Precambrian basement of Sarmatia according to[ Galetskiy, 1992] and its segmentation according to[Starostenko , Rusakov, 2015;Starostenko et al, 2017] with carried mantle plumes and superdeep fluids[Tsvetkova et al, 2017]: 1 -the border of the Dnieper-Donetsk depression; 2 -intersegmental faults of the depression (П-Пр -Pereyaslav-Khmelnitsky-Priluksky, В-Лг -Verkhovtsevsko-Lgovsky; 3 -faults (аintereoblock , б -intermegablock , в -interblock); 4 -suture zones of the first (a) and second ( б ) rank; 5 -transregional tectonic seams (Х-См -Kherson -Smolensk , Д-Бр -Donetsk-Bryansk); 6, 7 -kinematic types of faults (6 -thrust faults , 7 -strike-slip faults); 8 -isolines of the depth of the Moho section (km); 9 -state border. Letters in circles -the main segments within the DDD: Чн -Chernigovsky, Лх -Lokhvitsky, Iз -Izyumsky, Дб -Donbass.…”
mentioning
confidence: 99%
“…The re-vealed location of zones of superdeep fluid activation in the mantle indicates their relationship with the existence of oil-and-gas and probably hydrogen accumulations in the Dnieper-Donets Depression. Dr. Tatiana Tsvetkova and her colleagues [Tsvetkova et al, 2017[Tsvetkova et al, , 2020 have shown that not only plumes but also individual upward flows of deep fluid could be distinguished in the mantle beneath the platform. In particular, the Volyn-Orsha plume and four fluid flows (f2, f3, f4, f12) were distinguished in the vicinity of the Dnieper-Donets Rift (Fig.…”
mentioning
confidence: 99%